Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.383
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Consensus: Increasing Decentralization in Wikipedia Governance

Abstract: How does "self-governance" happen in Wikipedia? Through in-depth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 11 publications
(7 reference statements)
4
101
0
2
Order By: Relevance
“…In addition, they found that the first few votes in an election have a disproportionate effect on the final outcome of the election. Forte and Bruckman (2008) oun h W k pe gove n nce en s o ecen l ze: "As he commun y grows, it has become necessary for governance mechanisms to shift outward into the community. This decentralization was not entirely accidental; self-organization was dependent in part on the design of the technology and embedded in the philosophy of the community's oun e n e ly p c p n s." Fo e e al.…”
Section: Policiesmentioning
confidence: 99%
“…In addition, they found that the first few votes in an election have a disproportionate effect on the final outcome of the election. Forte and Bruckman (2008) oun h W k pe gove n nce en s o ecen l ze: "As he commun y grows, it has become necessary for governance mechanisms to shift outward into the community. This decentralization was not entirely accidental; self-organization was dependent in part on the design of the technology and embedded in the philosophy of the community's oun e n e ly p c p n s." Fo e e al.…”
Section: Policiesmentioning
confidence: 99%
“…The input can be merely consultative, as with Facebook's Site Governance initiative for gathering feedback on terms of service changes or U.S. President Obama's use of platforms for gathering ideas about implementing open governance. Or they can run deep in the DNA of the organization, such as in Wikipedia where contributors struggle to conduct distributed self-governance [6,14,21]. As we move outside hierarchical organizations, we believe we should expand our guiding theory to incorporate insights from political communication in order to more effectively design for these wider, more casual engagement efforts.…”
Section: Theory and Design For Public Deliberationmentioning
confidence: 99%
“…Wikipedia makes sure the agents are adaptive via a series of incentive and control mechanisms which are the foundation stones for the community order. The incentive mechanism stimulates users to join in the discussion of community rules [17] while the control mechanism asks for rather cautious edits on policy pages. Some policy pages are of rigid priority, which do not encourage much revision [18].…”
Section: Mechanism Of Spontaneous Order For Knowledgementioning
confidence: 99%